Knowledge, Attitude, and Practices of Iraqi Community Pharmacists Toward Emergency Contraceptives (Conference Paper )# - Basma Zuheir Al-Metwali; Juan Majid Shaukat (College of Pharmacy University of Baghdad, 2023)
Emergency contraceptives (ECs) are indicated for preventing the chance of unintended pregnancy that follows unprotected sexual intercourse in cases of incorrectly used regular contraceptives and in sexual assault. It is considered a safe choice to prevent pregnancy than abortion which is considered life threating. The aim of this study was to assess knowledge, attitude, and practices (KAP) of community pharmacists towards emergency contraceptives and their association with sociodemographic variables. This study was a cross sectional study conducted between August and September 2021 on a convenient sample of community pharmacists from Iraq. The survey tool was an online, self-administered questionnaire, in English language and a paper-based copy of the questionnaire was delivered face-to-face to some of the study participants. The questionnaire consisted of four parts, sociodemographic characteristics, knowledge, attitude and practices of community pharmacists toward emergency contraceptives.  A total of 212 community pharmacists participated in the study. Of the study participants, 67.9% were in the age range of (24-29) years, 61.8% were females,60% had less than 5 years of experience, the majority (73.1%) were from Baghdad. This study showed that the majority of community pharmacists (74%) had good knowledge and 95% of them had a very positive attitude. However, 51% of the participants had poor practice where 62.5% of the pharmacists did not make counselling during dispending on mechanism of action. This study results have shown no significant relationship between demographic characteristics and KAP of participants towards emergency contraceptives. The majority of the study participants had good knowledge and very positive attitude too, whereas poor practice was observed in more than half of the participants. Educational programs and training sessions are required to raise knowledge about the importance of emergency contraceptives and also to improve the dispensing practice of these products.